Nursing Care for Mr. M with a Diagnosis of Hypertension Using Innovative Finger Grip Relaxation Therapy at Ruwa Jurai Bhayangkara Hospital - Rismalia; Hardono; Sugiarto (INDOGENIUS, 2026)
Background & Objective: According to the WHO, hypertension remains a major problem, affecting 22% of the world's population. In Indonesia, an estimated 63,309,620 people suffer from hypertension, with a mortality rate of 427,218 deaths. The most common signs and symptoms experienced by people with hypertension when their blood pressure rises include headaches and pain in the back of the neck or nape. The purpose of this study was to provide nursing care to patients with hypertension using Finger Grip Relaxation Therapy as an intervention to reduce pain. Method: This study used a nursing care approach that focused on nursing actions for individuals with hypertension who complained of pain at the Ruwa Jurai Bhayangkara Hospital. Data collection used physical examination tools, KMB assessment forms, numerical scales, and the Finger Grip Relaxation Therapy SOP. Result: Based on the results of the intervention over 3 days, the pain scale decreased from 4 to 1. Conclusion: This therapy was proven effective in reducing pain.